(3QSGdI GdJeLjOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3SHMGf Gdedc GdLHGQ GdhGMO GdbgGQ SHMGf Gddg hGdMeO ddg hdG Edg EdG Gddg hGddg GcHQ dG JOQcg GdGHUGQ hdGjeKdI GdGacGQ hdGYQV ajSHb hLhOg s
(3BNQgG (B:s
(3hGdJfHjg Yf GdZadI hEaGVI GdHOGjI hcTa GdTHgI Efc hdi Pdc heHOAg Efc hdi GdELGHI hGdMeO ddg ai GdHOGjI hGdfgGjI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdadSaI hGdefWbs